Elevated levels of interleukin‐33 are associated with asthma: A meta‐analysis - Ranran Zhao; Yun Shi; Na Liu; Bin Li (Immunity, Inflammation and Disease)
Abstract Background Previous studies reported that patients with asthma showed higher levels of interleukin (IL)‐33 in peripheral blood, compared to healthy control (HCs). However, we also noticed that there were no significant differences of IL‐33 levels between controls and asthma patients in a recent study. We aim to conduct this meta‐analysis and evaluate the feasibility of IL‐33 in peripheral blood that may act as a promising biomarker in asthma. Methods Articles published before December 2022 were searched in these databases (PubMed, Web of Science, EMBASE, and Google Scholar). We used STATA 12.0 software to compute the results. Results The study showed that asthmatics showed higher IL‐33 level in serum and plasma, compared to HCs (serum: standard mean difference [SMD] 2.06, 95% confidence interval [CI] 1.12−3.00, I2 = 98.4%, p < .001; plasma: SMD 3.67, 95% CI 2.32−5.03, I2 = 86.0%, p < .001). Subgroup analysis indicated that asthma adults showed higher IL‐33 level in serum, compared to HCs, whereas no significant difference in IL‐33 level in serum was showed between asthma children and HCs (adults: SMD 2.17, 95% CI 1.09−3.25; children: SMD 1.81, 95% CI −0.11 to 3.74). The study indicated that moderate and severe asthmatics showed higher IL‐33 level in serum, compared to mild asthmatics (SMD 0.78, 95% CI 0.41−1.16, I2 = 66.2%, p = .011). Conclusions In conclusion, the main findings of present meta‐analysis suggested that there was a significant correlation between IL‐33 levels and the severity of asthma. Therefore, IL‐33 levels of either serum or plasma may be regarded as a useful biomarker of asthma or the degree of disease.